Ixodid ticks of African buffalo (Syncerus caﬀer), impala (Aepyceros melampus) and elephant (Loxodonta africana) in five protected park estates in the Zambezi valley, Zimbabwe - Moyo, Doreen Zandile; Chakuya, Jeremiah; Sungirai, Marvelous (Springer Nature, 2018)
Wildlife hosts many pathogens of economic importance and is considered as a reservoir of important tick-borne diseases of livestock in southern Africa. The species composition of ticks parasitizing buﬀalo (Syncerus caﬀer), impala (Aepyceros melampus) and elephant (Loxodonta africana) was investigated in ﬁve protected parks in the Zambezi valley, Zim-babwe. A total of 1104 adult ticks was collected from 75 adult animals comprising ﬁve buﬀaloes, ﬁve elephants and ﬁve impalas drawn from ﬁve protected wildlife parks. Five tick species belonging to two genera were recovered, with Rhipicephalus decoloratus being the most prevalent species in all the three animal groups. Amblyomma hebraeum was only recovered from buﬀaloes whereas Rhipicephalus zambeziensis was recovered from buﬀa-los and elephants. Signiﬁcant diﬀerences in mean tick species distribution and concentra-tion were observed amongst the wildlife parks and these appeared to be inﬂuenced by the number of hosts in each park. The study revealed that buﬀaloes are the major host of R. decoloratus in the Zambezi valley. The presence of these ixodid ticks within the Zambezi valley may have signiﬁcant ecological and economic impacts on wildlife conservation, domestic animals and human health.